Evidence-based cognitive retraining in elderly depressives - Rupesh Ranjan; Richa Priyamvada; Suprakash Chaudhury (Industrial Psychiatry Journal, 2023)
Background: Aging is a normal biological process, and its dynamic changes are beyond the control of human beings. The role of depression, fear, and anxiety in old age is preoccupied with unhappy thoughts, and loneliness leads to early deterioration in their cognitive performance which makes it difficult to perform daily activities and hence affects their quality of life. Aim: The present study was done to assess the effectiveness of cognitive retraining in elderly depressives and its effect on their quality of life. Materials and Methods: The study was done on a sample of 20 depressive elderly patients with an age range above 60 years diagnosed with ICD-10 criteria. The study was pre- and post-intervention, and the sampling method was purposive. Firstly to screen handedness, Annet's hand preference battery was used, to assess the depression in elderly, the geriatric depression scale was done, and for attention and memory, Digit Span Test (WAIS-R) and Wechsler Memory Scale (WMS) were administered, respectively. WHO-QOL BREF was done to know the quality of life of the patient. After preassessment, cognitive retraining tasks were introduced to the patients. A total of 15 sessions were taken within three months of follow-up and after that to evaluate the efficacy of an outcome of the cognitive retraining, post-assessment was done. Results: Improvement was noticed in elderly depressive patients in the area of cognitive domain, i.e., attention, recognition, shifting, fixedness, recall, and planning which showed improvement in quality of life and daily activities. Conclusion: In the remediation of cognitive deficits, cognitive retraining plays a very important role, and it helps the elderly population to live their life healthily and hence enhance their coping skills.